2013
DOI: 10.1093/brain/awt183
|View full text |Cite
|
Sign up to set email alerts
|

Positive feedback loop via astrocytes causes chronic inflammation in virus-associated myelopathy

Abstract: Human T-lymphotropic virus type 1-associated myelopathy/tropical spastic paraparesis (HAM/TSP) is a rare neurodegenerative disease characterized by chronic inflammation in the spinal cord. We hypothesized that a positive feedback loop driven by chemokines may be responsible for the chronic inflammation in HAM/TSP. We aimed to determine the identity of these chemokines, where they are produced, and how they drive chronic inflammation in HAM/TSP. We found that patients with HAM/TSP have extraordinarily high leve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
67
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 76 publications
(79 citation statements)
references
References 53 publications
(67 reference statements)
11
67
0
1
Order By: Relevance
“…Similar results were observed in experiments using cells isolated from sion profile (19). We suspected that these infected cells may infiltrate the CNS and trigger an inflammatory positive feedback loop, ultimately leading to chronic spinal cord inflammation (27). In the present study, we provided concrete evidence to support these theories on HAM/TSP pathogenesis, with a particular emphasis on the mechanism by which Tax can induce a proinflammatory phenotype intracellularly via transcriptional regulation.…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…Similar results were observed in experiments using cells isolated from sion profile (19). We suspected that these infected cells may infiltrate the CNS and trigger an inflammatory positive feedback loop, ultimately leading to chronic spinal cord inflammation (27). In the present study, we provided concrete evidence to support these theories on HAM/TSP pathogenesis, with a particular emphasis on the mechanism by which Tax can induce a proinflammatory phenotype intracellularly via transcriptional regulation.…”
Section: Discussionsupporting
confidence: 84%
“…Previously, we showed that these astrocytes produce CXCL10 in response to IFN-γ, and these levels are further amplified by the invading CXCR3 + cells (27). Together, these findings indicate that a positive feedback loop involving the recruitment of proinflammatory cells to the CNS is the source of chronic inflammation in HAM/TSP, and that the original trigger is the migration of IFN-γ-producing HTLV-1-infected cells to the CNS.…”
Section: Methodsmentioning
confidence: 53%
“…According to this hypothesis, HTLV-1-infected cells in the CNS would produce interferongamma that would induce astrocytes to secrete the chemokine CXCL10, which would be able to recruit more infected cells to the area via the chemokine receptor CXCR3, constituting a T helper type 1-centric positive feedback loop that would result in a state of chronic inflammation [13].…”
Section: Introductionmentioning
confidence: 99%
“…The neuroinflammatory process linked to myelopathy is thought to begin with IFN-γ secretion by infected CD4 + T cells in the CSF, stimulating C-X-C motif chemokine (CXCL)10 production by astrocytes. CXCL10, a chemokine promoting T-cell adhesion to endothelial cells and chemoattraction of inflammatory cells, increases mononuclear infiltration into the CSF creating a positive feedback loop for chronic inflammation in HAM/TSP [24]. In patients with HAM/TSP, levels of IFN-γ-producing T cells with loss of immune suppressive function have been shown to correlate with clinical severity [25].…”
Section: Neuroinfectious Diseasementioning
confidence: 99%